Megacam: A Wide-Field CCD Imager for the MMT and Magellan. (4th January 2016) - McLeod, Brian; Geary, John; Conroy, Maureen; Fabricant, Daniel; Ordway, Mark; Szentgyorgyi, Andrew; Amato, Stephen; Ashby, Matthew; Caldwell, Nelson; Curley, Dylan; Gauron, Thomas; Holman, Matthew; et al.
Abstract: Megacam is a large-format optical camera that can be operated at the f/5 Cassegrain foci of the MMT on Mount Hopkins, Arizona, and the Magellan Clay telescope at Las Campanas Observatory, Chile. Megacam's focal plane is composed of 36 closely packed e2v CCD42-90 CCDs, each with 2048 × 4608 pixels, assembled in an 18, 432 × 18, 432 array. Two additional CCD42-90s are provided for autoguiding and focus control. The CCDs have 13.5 μm square pixels that subtend0 ''.\! 08 at the f/5 foci, yielding a 25 ′ × 25 ′ field-of-view. The camera system includes a focal plane shutter, two filter wheels, two liquid nitrogen reservoirs, a central chamber that holds the CCD mosaic array, and two electronics boxes. Megacam is equipped with a variety of broadband and narrowband filters. Software features include automatic calculation of twilight flat exposure times.